1998
DOI: 10.1159/000027584
|View full text |Cite
|
Sign up to set email alerts
|

A CT Study of the Course of Growth of the Maxillary Sinus: Normal Subjects and Subjects with Chronic Sinusitis

Abstract: We measured the maxillary sinus volume of normal children and those with bilateral chronic sinusitis by coronal CT scan of the paranasal sinus, and compared the results with findings previously obtained from adult patients. The distribution of mean maxillary sinus volume by age group from 4–9 to 70–79 years exhibited a monomodal pattern with a peak in the 20s in both the normal group and the surgical therapy group. The maxillary sinus volumes of children aged 10–15 years and adults tended to be smaller in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 7 publications
(15 reference statements)
4
30
1
Order By: Relevance
“…But previous studies have shown that volume of maxillary sinus changes with age in males and females. 10,16,18 According to Ikeda et al 10 in age group of 4e9 years, females showed larger sinus whereas in age group of 10e15 years, males showed larger volumes. Karakas and Kavakli 16 also found out that in age group of 5e10 years females had larger maxillary sinus volume than males and in the age group of 11e15 years, males showed an increase in the volume over females.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…But previous studies have shown that volume of maxillary sinus changes with age in males and females. 10,16,18 According to Ikeda et al 10 in age group of 4e9 years, females showed larger sinus whereas in age group of 10e15 years, males showed larger volumes. Karakas and Kavakli 16 also found out that in age group of 5e10 years females had larger maxillary sinus volume than males and in the age group of 11e15 years, males showed an increase in the volume over females.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, females have larger sinuses than males from age 4e10. 10,16 However, in adults, males show larger sinuses than females.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maxillary sinus growth persists until 14-16 years of age; gender differences have been reported in sinus growth [14]. Therefore, this study was performed at the appropriate time to determine differences between a CRS group and normal controls without the interference of gender.…”
Section: Discussionmentioning
confidence: 99%
“…The average age was 41.61±12.95, ranging forming the base area of the alveolar process 11 . The maxillary sinus grows rapidly as permanent tooth eruption until 15-20 years on the average, but the sinus floor can be expanded downward with the loss of the maxillary posterior area [12][13][14] . Maxillary sinus bone graft is largely divided into 2 types: one is the lateral approach introduced in the 1970s by Tatum 15 , and the other is the alveolar ridge approach introduced in the 1980s by Summers 16 .…”
Section: Methodsmentioning
confidence: 99%